Relationship between Health-related Quality of Life and Selected Variables of Cardiac Patients - Kumar, Vinay; Kaur, Harleen; P. N. Priya, J.; Pugazhendi, Sanchita (International Journal of Nursing Research, 2023)
Aim: The aim of the study was to find the association between health-related quality of life (HRQOL) and cardiac disease patient. Materials and Methods: A descriptive research design was used to find the relationship between HRQOL of cardiac disease patients, 158 samples were selected from Himalayan Hospital, Dehradun, Uttarakhand, by purposive sampling technique. Data were collected by SF-36 tool for which the test-retest method was used to find the reliability of the standardized SF-36 tool and it was established as r = 0.97. Data for HRQOL were collected with structured interview method. Results: The finding shows that there was a significant relationship between domains of HRQOL and selected variables. Domain of HRQOL, that is, social functioning (P = 0.002) with age in years, domain of HRQOL, that is, general health (P = 0.001) with educational status, and domain of HRQOL, that is, social functioning (P = 0.004) with occupational status of sociodemographic variables of participants. Conclusion: The study concluded that the domains of HRQOL of cardiac patients were affected by their selected variables.